PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN REACT PADA POKOK BAHASAN TRANSFORMASI UNTUK PESERTA DIDIK KELAS IX SMP - VANI ARISA (Jurnal Edukasi dan Penelitian Matematika, 2021)
According to conclusion of preliminary research in ninth-grade showed that the most of the mathematics learning outcomes have not qualify the mark determined and they were passive in the learning process. The factor of this case  caused by learning tools still not optimal. Based on this situation, researcher doing development on the  mathematic’s learning tools, as like as lesson plan  (RPP) and student’s  worksheets (LKPD)  on  REACT  learning model to supply learning experiences and great effect in student’s learning activities as long as learning process. In this research, researcher were collected the data through of observation, teachers interview, and another coherent research sources. The main research’s subjects are students in ninth of junior high school with different cognitive ability. This research  based on plomp design, this design contain are preliminiary research phase,  prototype phase, and  assessment phase. Come from result of data analysis proved  that REACT learning tools was qualify as very valid criteria of content and construction, afterthat itself  qualify to practical criteria of  execution and effectiveness in time use according to students questionnaires.  Keywords—Development design research, learning tools, REACT learning mode, transformation